Adverse events and treatment interruption in tuberculosis patients with and without HIV co-infection. Issue 9 (14th July 2006) - Breen, R A M; Miller, R F; Gorsuch, T; Smith, C J; Schwenk, A; Holmes, W; Ballinger, J; Swaden, L; Johnson, M A; Cropley, I; Lipman, M C I
Abstract : Background: Serious treatment associated adverse events are thought to occur more frequently in individuals with tuberculosis (TB) who are co-infected with HIV. A study was undertaken to assess the frequency of serious (grade III/IV) adverse events and interruption of anti-TB treatment in the era of effective antiretroviral therapy. Methods: The incidence of serious adverse events was retrospectively compared in 312 individuals treated for TB, 156 of whom were co-infected with HIV. Results: 111 HIV infected individuals (71%) received highly active antiretroviral therapy at the same time as anti-TB treatment. Serious adverse events were recorded in 40% HIV infected and 26% HIV uninfected individuals (p = 0.008). Peripheral neuropathy and persistent vomiting were more common in co-infected patients (p<0.001; p = 0.006), although all cause interruption of anti-TB treatment occurred with similar frequency in the two groups (13% in HIV infected patients and 15% in HIV uninfected patients; p = 0.74). In 85% of HIV infected patients and 87% of HIV uninfected individuals this was due to hepatotoxicity, which typically presented within 2 months of starting treatment. The median delay in restarting treatment was 4 weeks, so most individuals required full TB re-treatment. Conclusion: Despite a greater rate of serious (grade III/IV) adverse events among HIV infected individuals, discontinuation of anti-TB treatment occurred with a similar frequency in HIV infected and HIV uninfected individuals.